PENERAPAN SISTEM PEMBAYARAN DIGITAL QRIS SEBAGAI UPAYA PENINGKATAN DAYA SAING UMKM DI DESA SINGARAJAN DALAM ERA EKONOMI DIGITAL - Ahmad Rayhan; Medina Masri; Siti Mutiawati; Siti Fatiha; Diego Mesakh Arapenta Ginting; Hanifah Afratunisa Husen (Devote: Jurnal Pengabdian Masyarakat Global, 2025)
Singarajan Village has economic potential through Micro, Small, and Medium Enterprises (MSMEs); however, most transactions are still cash-based, making them less efficient and more risky. To support digital economic transformation and financial inclusion, the community service team implemented the Quick Response Code Indonesian Standard (QRIS) as an integrated digital payment system. The method applied was a participatory approach through socialization, training, transaction simulations, and assistance with merchant registration for QRIS. The activities involved MSME actors, the village government, and support from Bank Indonesia and BRI as strategic partners. The results showed an increase in MSMEs’ understanding and skills in using QRIS, as evidenced by the growing number of merchants registering their businesses and their willingness to adopt cashless transactions. QRIS has proven to provide benefits such as payment convenience, transaction security, time efficiency, and opportunities to expand into digital markets. The recommendations include continuous mentoring, improved digital literacy, and strengthened network infrastructure to ensure the sustainability of QRIS adoption. Thus, QRIS has the potential to become an entry point for transforming rural economies to be more inclusive, efficient, and competitive.